Efektivitas Penerapan Metode Hypnoteaching Dalam Meningkatkan Aktivitas Belajar Siswa - ida bagus alit arta wiguna (Universitas Negeri Makassar, 2020)
Teachers are required to have methodological abilities in the design and implementation of learning. The application of Hypnoteaching method in increasing learning activities greatly helps the learning process in the classroom and increases learning motivation which has an impact on increasing learning activities. This research uses a combination of sequential exploratory research methods. Combined research methods that combine qualitative and quantitative research sequentially where in the first phase of research using qualitative methods and in the second stage quantitative methods. Qualitative methods function to support hypotheses in certain cases or limited samples and quantitative methods function to support hypotheses in a wider population. The application of the Hypnoteaching method given by the teacher in class X is very effective in making the passive classroom atmosphere become calm and active when given a Hypnoteaching method stimulus. The fun atmosphere of learning in the classroom will cause students to feel at home while learning in class. From the results of the calculation of the average value and absorption of the above students obtained results for the average of the overall learning outcomes of students in class X Mipa 6 is 88 and the absorbency obtained from the average score of students is 88%. These results indicate that the average score or value of students is in the range of 61-100 with the category of Effective and Very Effective.